2021
DOI: 10.3390/ani11113037
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Combination of Lysolecithin, Synthetic Emulsifier, and Monoglycerides on Growth Performance, Intestinal Morphology, and Selected Carcass Traits in Broilers Fed Low-Energy Diets

Abstract: This study aimed to evaluate the effect of supplementing a combination of lysolecithin, synthetic emulsifier, and monoglycerides (LEX) on growth performance, intestinal morphology, and selected carcass traits in broilers fed low-energy diets without added oil. Three hundred one-day-old Arbor Acres (AA) broilers (40.3 ± 3.3 g) were assigned to two dietary treatments with six replicates of 25 birds each and were fed a control low-energy diet without added oil supplemented with 0 and 250 g/t of LEX for 30 days. G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 44 publications
2
7
0
Order By: Relevance
“…The recommended Mn content for broilers is 120 mg/kg during 1–3 weeks and 100 mg/kg during 4–6 weeks by the Feeding Standard of Chicken in China. Additionally, we searched recent related articles on broiler experiments in Animals and also found that the amount of added Mn in the diet was around 100 mg/kg [ 18 , 19 , 20 , 21 , 22 ]. So we added 100 mg/kg Mn in the form of MnSO 4 as the positive control.…”
Section: Methodsmentioning
confidence: 99%
“…The recommended Mn content for broilers is 120 mg/kg during 1–3 weeks and 100 mg/kg during 4–6 weeks by the Feeding Standard of Chicken in China. Additionally, we searched recent related articles on broiler experiments in Animals and also found that the amount of added Mn in the diet was around 100 mg/kg [ 18 , 19 , 20 , 21 , 22 ]. So we added 100 mg/kg Mn in the form of MnSO 4 as the positive control.…”
Section: Methodsmentioning
confidence: 99%
“…Two basal control diets were formulated: a normal energy ( NE ) control, formulated to meet Aviagen nutrient requirements, and a low energy ( LE ) control with a 90 to 100 kcal reduction in energy, dependent on phase, compared to the NE. This downspec is based on previous commercial and academic experience ( Ghazalah et al, 2021 ). NE and LE diets were isonitrogenous and provided balanced mineral profiles.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, lysolecithin is known to become incorporated into the phospholipid bi-layers of cells, inducing local curvatures and alterations in protein channel formation, thereby improving the fluidity and permeability of the membrane ( Lundbaek and Andersen, 1994 ) and inducing epigenetic alterations related to collagen deposition ( Brautigan et al, 2017 ). LEX supplementation results in improved villus height ( Brautigan et al, 2017 ; Ghazalah et al, 2021 ) and increased absorptive capacity, driving improvements in nutrient digestibility beyond lipid absorption ( Wealleans et al, 2020a ). These nonlipid-related effects may explain recent work by Ghazalah et al (2021) , which showed that the ability of LEX to improve feed efficiency and growth, both in “on top” and reformulated diets, is not only linked to the utilization of added fat in high-density diets, but can also improve the performance and profitability of birds fed low-energy diets containing no added fat.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Monoglycerides are a class of nonionic surfactants with a lipophilic long-chain alkyl group and two hydrophilic hydroxyl groups. Monoglycerides have emulsifying [ 1 ], antistatic [ 2 ], lubricating [ 3 ], and antibacterial properties [ 4 ] and are widely used in various fields, such as food [ 5 ], pharmaceuticals [ 6 ], cosmetics [ 7 ], detergents [ 8 ], and chemicals [ 9 ]. Currently, the large-scale production of monoglycerides is mainly achieved through chemical methods, including grease hydrolysis, fatty acid esterification, and grease glycerolysis [ 10 ].…”
Section: Introductionmentioning
confidence: 99%